Integrasi Media Digital Canva dalam Pembelajaran Menulis Teks Biografi sebagai Penguatan Kreativitas Peserta Didik Kelas X - Wahyuning Larasati; Sri Muryati; Wahyu Dini Septiari (STKIP Singkawang, 2025)
This study aims to describe the application of Canva's digital media in the learning process of writing biographical texts for grade X students and to describe the exploration of students' creativity through the use of Canva in biographical text writing. This research method uses qualitative with a descriptive presentation of the research results. This data collection technique uses observation, interviews, questionnaires and documentation studies. Data analysis in this study includes data collection, data reduction, data display, and conclusion drawing data. The results of this study explain the application of Canva digital media in learning to write biographical texts which includes the planning stage carried out by the teacher, the implementation stage and the evaluation stage. Then explore students' creativity in writing biographical text in the form of infographics using Canva. Thus, students can develop ideas and present biographical texts in the form of posters or infographics so as to create an interesting and informative text display to read.